COMPARACIÓN DE LA FUERZA ADHESIVA Y EL TIPO DE FALLA DE DOS SISTEMAS ADHESIVOS PARA ORTODONCIA (2011)
Objective: To compare the bond strength and failure mode between total and self-etching systems used for brackets cementation.Methods: Twenty human first premolars were randomly divided into two groups: 10 for the total etching system (Transbond™ XT, 3M Unitek, St. Paul, Minnesota, USA) and 10 for the self-etching system (Transbond™ Plus Self Etching Primer + Transbond™ XT, 3M Unitek, St. Paul, Minnesota, USA). Standard brackets (Ortho Organizers, California, USA) were cemented, and after 24 hours submitted to 5000 thermal cycles. Subsequently, shear bond strength tests were performed applying force at the bracket/enamel interphase using an universal testing machine (Instron®) at 1.5 mm/min crosshead speed. Finally, enamel surfaces and bracket bases were observed using a stereomicroscope (Stemi 2000C, Carl Zeiss, Göttingen, Germany).Results: The results, in terms of bond strength, showed a statistical significant difference (p<0.05) between the two adhesive systems, presenting higher values the total-etching system (28,98MPa vs. 18,67MPa). The predominant failure modes presented for both systems were at the adhesive-enamel interphase (80% and 70%).Conclusion: Bond strength and failure mode are influenced by the dental substrate pre-treatment and the chemical composition of the adhesive. Therefore, the in-vitro bond strength obtained when a self-etching system is used in orthodontics, produce enough micromechanical retention with lower risk of damage to the dental tissue.